Antibacterial activities of protein extracts from andrographis paniculata, tinospora crispa and centella asiatica - Md Zin, Noor Hasniza; Ahmad, Nurul Fatihah; Muhamad Bunnori, Noraslinda; Abdul Wahab, Widya; Haron, Normah (Kulliyyah of Medicine, International Islamic University Malaysia, 2016)
Introduction: Andrographis paniculata, Tinospora crispa and Centella asiatica are known to have various pharmacological functions. This research was carried out to investigate the antibacterial activities of protein extracts from A. paniculata, T. crispa and C. asiatica.Methods:Total soluble proteins from these herbs were extracted using a modified TCA/acetone method.The protein extracts were then quantified using Bradford assay and separated using SDS-PAGE.The antibacterial activities were determined by disc diffusion method.Results and discussion:T. crispa had a significantly higher amount of proteins (83.86 ±0.4 µg/µl) compared to A.paniculata (81.57±0.4 µg/µl) and C. asiatica (78.93 ±0.5 µg/µl). The proteins separated by SDS-PAGE were ranged from 30kDa to 260kDa, 25kDa to 110kDa and 25kDa to 160kDa for A. paniculata, T. crispa and C. Asiatic, respectively. The high abundance proteins were observed in A. paniculata and T. crispa but not in C.asitica. Protein extracts from C. asiatica have demonstrated antibacterial activity against all tested bacteria with the diameter of inhibition zone of 11.0 ± 0.5 mm, 12.3 ± 0.6 mm, 10.7 ± 0.7 mm and 20.0 ± 0.8 mm against B. cereus, S.aureus, K. pneumonia and S. typhimurium respectively. Meanwhile, protein extracts of A. paniculata showed a positive antibacterial activity only against B.cereus (13.7 ± 0.4 mm), S. aureus (7.0 ± 0.8 mm) and S. typhimurium (11.5 ± 0.3 mm). Protein extracts from T. crispa only showed a positive antibacterial activity against B.cereus (9.7 ± 0.5 mm).Conclusion:There is a constant need in the discovery of new antibiotics for the treatment of infectious diseases.